Human Instruments—(Maybe Not So) Radical Inclusion - Gehlhaar-Matossian, Vahakn; Cormier, Zoe (Circuit, 2022)
Human Instruments has its roots in experimental music and interaction. The company creates beautifully made, professional, accessible music technologies to level the playing field of music performance for disabled musicians. This article focuses on the need for growth and change in this field, as well as the history, present and future of the organisation.